22 Audit of Management of Patients with Heart Failure following non-STEMI and Use of Aldosterone Antagonists. (3rd June 2016) - Buckledee, Olivia; Ismail, Yasmin; Nightingale, Angus
Abstract : Background: The presence of heart failure following a non-ST elevation myocardial infarction (non-STEMI) is associated with a worse prognosis. Current UK and European Guidelines recognise the importance of identifying these higher risk patients and offering them disease modifying therapies including drugs and devices. We wanted to find out of these guidelines were being followed in a busy Heart Attack Centre in the South West of England; in particular, whether a mineralocorticoid receptor antagonist (MRA) was being prescribed to those with impaired LV function and either diabetes or signs heart failure. Methods: We performed a retrospective audit of consecutive patients identified as having non-STEMI on the MINAP database form April 2014 to March 2015. We assessed: How many received an echocardiogram during their index admission; Compliance with NICE recommended post MI medications on discharge; Implications for device implantation rates according to NICE and ESC guidelines. Results: 176 patients (mean age 70 years, 64% male) were recorded on the MINAP database with non-STEMI in the study period. 71% (125/176) had an echocardiogram during the index admission. 42% (53/125) had good left ventricular (LV) function and 30% (38/125) had moderately or severely impaired LV function (EF < 40%). Of those with impaired LV function post non-STEMI, 82% (31/38) either had diabetes or signs of pulmonary oedema; 6 of these had a documented contra-indication to a MRA. 56% (14/25) were prescribed a MRA in accordance with the NICE guidelines compared to > 95% compliance with guidelines recommending ACEi/BB/statin/antiplatelet agents. Mean length of stay for those with impaired LV function was 7.9 days. 71% (27/38) of the impaired LV function patients were followed up by our cardiology team with 11 referred back to their local hospital for follow up. 41% (11/27) had a repeat echo after at least one month to reassess LV function and assess requirement for implantable devices. Conclusions: Nearly a third of patients had significantly impaired LV function following non-STEMI. Whilst most post-MI drugs were prescribed >95% in compliance with the NICE guidelines, MRAs (spironolactone and eplerenone) were only prescribed in around half of suitable cases. The reasons for this could include poor documentation of contraindication to MRA or lack of awareness of the guidelines. Follow-up reassessment of LV function after at least a month to detect functional recovery or indication for device therapy was also poor. Opportunities to prevent sudden death or worsening heart failure by implanting ICD or CRT devices could therefore have been missed. Management of non-STEMI patients complicated by heart failure might benefit from a closer link between the acute coronary syndrome and the heart failure teams to improve outcomes and reduce length of stay for patients.